Formation of attitudes for success in the jockey career - Paredes Tarazona, Mildred (2002)
This year studied to a sample of 50 Jockeys and apprentices of the Race course of Monterrico (File-Peru) representative of the total population. They participate in the Program of Labor Formation, created in 1985. They are young people who emphasize by their high level of abstract reasoning and space reasoning, its visual motor and synesthetic skills, direction and motivation by estatus social and enjoys the risk (increase of noradrenaline) that provides the flat racing of pure blood, own activity of this one sport occupation of high competition and risk to him; one investigated his Social attitudes towards the Personal Organization, Abilities, Discipline in the Work and the Meaning of the Race and evaluates the attitudes towards successful practices by means of its comportamentales habits; by means of one it climbs ad hoc for the investigation. Also, the "Scale M-L" of Vicuña and Cols. is used to correlate these attitudes with its level of profit motivation. The evaluated group presents/displays the predominance of the affiliation motivation, coherence between the self-evaluation and the behaviors and oscillates between the levels acceptable and good as far as attitudes and behaviors of the successful jockey.